Is Marriage a Turning Point? Evidence from Cash Holdings Behaviour - Sabri Boubaker (British Journal of Management, 2023)
Given that marriage transforms people, with wide-ranging and long-lasting impacts, we examine the role of CEOs' marital status on firms' cash holdings behaviour. Using a large sample of US-listed firms, we find that single CEOs stockpile more cash than their married counterparts do. Our finding is robust to controlling for various CEO characteristics, CFO influence, tackling endogeneity concerns and using alternative measures of cash. Moreover, we show that exogenous CEO turnover resulting in appointments of single (married) CEOs increases (decreases) cash holdings. Additional results show that single-CEO firms practise a more conservative payout policy and save more cash from operating and financing cash flows. Consistent with agency theory, single CEOs extract more compensation from the accumulated cash, leading to a lower value of cash holdings. External corporate governance mechanisms mitigate the relationship between single CEOs and cash holdings. Our results show that single-CEO firms are more prone to agency problems.